2021
DOI: 10.1021/acs.jpcb.0c10883
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations Study on the Shear Viscosity, Density, and Equilibrium Interfacial Tensions of CO2 + Brines and Brines + CO2 + n-Decane Systems

Abstract: The shear viscosity, density, and interfacial tensions (IFT) of two systems, namely, brine and brine/n-decane, blended with carbon dioxide (CO2) were investigated via molecular dynamics simulations over broad ranges of temperature, pressure, CO2 mole fraction, and brine concentration. The operating conditions for the molecular simulations to be studied are similar to the CO2 geological storage processes. The effects of temperature, pressure, and concentrations on the viscosity and IFT have been investigated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 48 publications
(106 reference statements)
3
22
0
Order By: Relevance
“…Past studies have shown that the IFT of the alkane + water + CH 4 /CO 2 systems is more similar to that of the corresponding alkane + water system alone. 25,35,36,[38][39][40][41][42][43]45 Also, the IFT of the decane + brine + CH 4 / CO 2 systems was more similar to that of the corresponding decane + brine system alone. 26,29,39,44,45 The IFTs of all these systems decreased with temperature.…”
Section: Interfacial Tensionmentioning
confidence: 99%
See 4 more Smart Citations
“…Past studies have shown that the IFT of the alkane + water + CH 4 /CO 2 systems is more similar to that of the corresponding alkane + water system alone. 25,35,36,[38][39][40][41][42][43]45 Also, the IFT of the decane + brine + CH 4 / CO 2 systems was more similar to that of the corresponding decane + brine system alone. 26,29,39,44,45 The IFTs of all these systems decreased with temperature.…”
Section: Interfacial Tensionmentioning
confidence: 99%
“…25,35,36,[38][39][40][41][42][43]45 Also, the IFT of the decane + brine + CH 4 / CO 2 systems was more similar to that of the corresponding decane + brine system alone. 26,29,39,44,45 The IFTs of all these systems decreased with temperature. For instance, the simulation value of the IFT of the decane + water system (20 MPa) decreased from about 47.8 mN m À1 at 323 K to about 36.5 mN m À1 at 443 K. 39 It was found that the IFTs of these systems generally increased with pressure.…”
Section: Interfacial Tensionmentioning
confidence: 99%
See 3 more Smart Citations